Quality of inpatient paediatric and newborn care in district hospitals: WHO indicators, measurement, and improvement - English, M; Aluvaala, J; Maina, M; Duke, T; Irimu, G (Elsevier, 2023)
Poor-quality paediatric and neonatal care in district hospitals in low-income and middle-income countries (LMICs) was first highlighted more than 20 years ago. WHO recently developed more than 1000 paediatric and neonatal quality indicators for hospitals. Prioritising these indicators should account for the challenges in producing reliable process and outcome data in these settings, and their measurement should not unduly narrow the focus of global and national actors to reports of measured indicators. A three-tier, long-term strategy for the improvement of paedicatric and neonatal care in LMIC district hospitals is needed, comprising quality measurement, governance, and front-line support. Measurement should be better supported by integrating data from routine information systems to reduce the future cost of surveys. Governance and quality management processes need to address system-wide issues and develop supportive institutional norms and organisational culture. This strategy requires governments, regulators, professions, training institutions, and others to engage beyond the initial consultation on indicator selection, and to tackle the pervasive constraints that undermine the quality of district hospital care. Institutional development must be combined with direct support to hospitals. Too often the focus of indicator measurement as an improvement strategy is on reporting up to regional or national managers, but not on providing support down to hospitals to attain quality care.